Cryo-electron tomography pipeline for plasma membranes - Willy W. Sun; Dennis J. Michalak; Kem A. Sochacki; Prasanthi Kunamaneni; Marco A. Alfonzo-Méndez; Andreas M. Arnold; Marie-Paule Strub; Jenny E. Hinshaw; Justin W. Taraska (Nature Communications)
Abstract Cryo-electron tomography (cryoET) provides sub-nanometer protein structure within the dense cellular environment. Existing sample preparation methods are insufficient at accessing the plasma membrane and its associated proteins. Here, we present a correlative cryo-electron tomography pipeline optimally suited to image large ultra-thin areas of isolated basal and apical plasma membranes. The pipeline allows for angstrom-scale structure determination with subtomogram averaging and employs a genetically encodable rapid chemically-induced electron microscopy visible tag for marking specific proteins within the complex cellular environment. The pipeline provides efficient, distributable, low-cost sample preparation and enables targeted structural studies of identified proteins at the plasma membrane of mammalian cells.